1998
DOI: 10.3141/1639-16
|View full text |Cite
|
Sign up to set email alerts
|

Correction of Field Skid Measurements for Seasonal Variations in Texas

Abstract: Findings are presented from a research study conducted in Texas to determine the significance of seasonal variation in skid measurements. Six bituminous highway pavement sections, two each from three different climatic regions, were monitored over a period of more than 18 months. Monitoring included collection of wet pavement skid resistance data using a locked-wheel skid trailer that met the specifications of ASTM E-274. These measurements were made at biweekly intervals in two of the three climatic regions a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 3 publications
2
35
0
1
Order By: Relevance
“…Previous studies concluded that when the friction testing was conducted in wet regions, the water film may cover the pavement surface and act as a lubricant, which can reduce the contact between the tires and surface aggregate. This is one of the reasons why wet-pavement surfaces exhibit lower friction than dry pavement surfaces [8]. Some researchers attributed the seasonal variation of friction to rainfall.…”
Section: Background On Pavement Frictionmentioning
confidence: 99%
“…Previous studies concluded that when the friction testing was conducted in wet regions, the water film may cover the pavement surface and act as a lubricant, which can reduce the contact between the tires and surface aggregate. This is one of the reasons why wet-pavement surfaces exhibit lower friction than dry pavement surfaces [8]. Some researchers attributed the seasonal variation of friction to rainfall.…”
Section: Background On Pavement Frictionmentioning
confidence: 99%
“…Seasonal variations can have a significant effect on pavement friction (Fwa 2005). This effect can be explained by changes in temperature and precipitation (Jayawickrama and Thomas 1998). Overall friction is lower in summer months compared to other times of the year.…”
Section: Introductionmentioning
confidence: 88%
“…Deney uygulanırken yüzeydeki toz, kum, yağ ve diğer yapancı maddelerin ölçüm sonuçlarına etkisini azaltmak için yüzey bir fırça ile temizlenmelidir [33]. Su basıncından kaynaklanabilecek herhangi bir etkiye karşı su tankı DFT cihazından en az 0,6 m yüksekte olmalı ve her deney öncesi doldurulmalıdır.…”
Section: şEkil 4 Dft Cihazında Dönen Diske Etkiyen Kuvvetlerunclassified